Adapting a Low-Cost Selective Compliant Articulated Robotic Arm for Spillage Avoidance. (December 2016) - McMorran, Darren; Chung, Dwayne Chung Kim; Li, Jonathan; Muradoglu, Murat; Liew, Oi Wah; Ng, Tuck Wah
Flexible automation systems provide the needed adaptability to serve shorter-term projects and specialty applications in biochemical analysis. A low-cost selective compliant articulated robotic arm designed for liquid spillage avoidance is developed here. In the vertical-plane robotic arm movement test, the signals from an inertial measurement unit (IMU) and accelerometer were able to sense collisions. In the horizontal movement test, however, only the signals from the IMU enabled collision to be detected. Using a calculation method developed, it was possible to chart the regions where the obstacle was likely to be located when a collision occurred. The low cost of the IMU and its easy incorporation into the robotic arm offer the potential to meet the pressures of lowering operating costs, apply laboratory automation in resource-limited venues, and obviate human intervention in response to sudden disease outbreaks.